Design and impact of water treaties Managing climate change - Zentner, Matthew; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This study presents a unique way to utilize the existing literature to explain the success of treaties in managing hydrologic stress. Literature-derived core concepts are summarized as seven treaty mechanisms categories (specificity, uncertainty management, enforcement, communications, flexibility, integrativeness, and scale) and are hypothesized as important for shaping the institutional resiliency of a treaty. Treaty design is shown to have a relevant and important role in shaping basin management so that nations may better achieve their goals in a changing climate.
Introduction -- Literature Review -- Hypotheses, Definitions, and Explanatory Mechanisms -- Data and Methods: Treaties, Power, Scarcity, and Conflict -- Results -- Case Studies-Application of the Results -- Conclusions.
Keywords: Earth sciences; Environmental management; Climate change; Hydrogeology; Atmospheric sciences; Water pollution; Earth Sciences; Hydrogeology; Water Policy/Water Governance/Water Management; Climate Change/Climate Change Impacts; Atmospheric Sciences; Waste Water Technology / Water Pollution Control / Water Management / Aquatic Pollution; Environmental Management; Electronic books